Final exam [large type] - Barbieri, Maggie (Barbieri, Maggie. Murder 101 mystery., 2010)
St. Thomas the college north of New York where Alison Bergeron teaches has had its share of scandals so when a Resident Director goes missing they keep it quiet by tapping Alison as a replacement. A stay in the dorms is like hard time and she will do anything to avoid it. Her way out: find the reluctant RD and drag him back. Luckily she doesn't have to look further than the drugs he's hidden to get her boyfriend Detective Bobby Crawford on the case.